Non take up of social benefits in Greece and Spain - Manos Matsaganis; Horacio Levy; Maria Flevotomou (University of Essex, Institute for Social and Economic Research (ISER), 2010)
Even though interest in non take up of social benefits is considerable in many European countries, the topic is under-researched in southern Europe. The paper provides preliminary estimates of the extent of non take up of two pairs of means-tested retirement benefits in Greece and Spain. The benefits examined are (i) the minimum pension supplements 'pensioner social solidarity benefit EKAS' and 'complementos por mínimos', and (ii) the social pensions 'pension to uninsured elderly' and 'pensión de jubilación no contributiva'. The paper finds that non take up of social benefits in the two countries is rather extensive, examines the methodological difficulties inherent in the analysis of non take up, and concludes with a discussion of the results and their implications.
Keywords: D31; H31; H53; I38; 330; non take up; means-tested benefits; Greece; Spain; Mindestrente; Soziale Mindestsicherung; Alte Menschen; Griechenland; Spanien